The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011 Australasian Telecommunication Networks and Applications Conference (ATNAC) 2011
DOI: 10.1109/atnac.2011.6096653
|View full text |Cite
|
Sign up to set email alerts
|

Wireless hop-by-hop credit-based flow control extended to source for stable best effort traffic

Abstract: Abstract-Data traffic is expected to grow faster than capacity in future wireless networks. Therefore it will become unavoidable to deal with congestion. Bottlenecks are located on the wireless links because back-haul and Internet are overprovisioned. Traffic routed towards the user terminal (UT) in down-link direction keeps coming in through a big pipe until it reaches the base station (BS). The following wireless links can only carry a limited data rate due to congestion. In a multi-hop situation buffers bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…III and implemented at RNs. As mentioned in [8], DeNB only implements the TFCS since DeNB doesn't have the handover forwarding problem. The detailed simulation setting for all flow control schemes were configured as in Table II.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…III and implemented at RNs. As mentioned in [8], DeNB only implements the TFCS since DeNB doesn't have the handover forwarding problem. The detailed simulation setting for all flow control schemes were configured as in Table II.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In [7], the credit-based flow control scheme was adopted to alleviate the buffer-overflow problem in multihop cellular network. In [8], the authors further indicated that the bufferoverflow problem does not merely occur at RN. This problem also emerges at DeNB due to the high-speed wired backhaul.…”
Section: Literature Reviewmentioning
confidence: 99%